2004
DOI: 10.1017/s0016672304007013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of two sister species in the Drosophila melanogaster subgroup, D. yakuba and D. santomea

Abstract: We performed genetic analysis of hybrid sterility and of one morphological difference (sex-comb tooth number) on D. yakuba and D. santomea, the former species widespread in Africa and the latter endemic to the oceanic island of São Tomé, on which there is a hybrid zone. The sterility of hybrid males is due to at least three genes on the X chromosome and at least one on the Y, with the cytoplasm and large sections of the autosomes having no effect. F1 hybrid females carrying two X chromosomes from either specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
64
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 55 publications
1
64
0
Order By: Relevance
“…This variation makes the sex comb an attractive model for understanding the genetic basis of morphological evolution and the interaction between developmental pathways and natural selection in shaping animal form. Quantitative-genetic analyses in several species have shown that interspecific and intraspecific differences in sex comb size are determined by multiple, as yet unidentified, loci (True et al 1997;Macdonald and Goldstein 1999;Nuzhdin and Reiwitch 2000;Coyne et al 2004;Tatsuta and TakanoShimizu 2006;Graze et al 2007). At the same time, developmental-genetic approaches are beginning to elucidate the molecular pathways involved in the specification and differentiation of sex combs (Barmina et al 2005;Barmina and Kopp 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This variation makes the sex comb an attractive model for understanding the genetic basis of morphological evolution and the interaction between developmental pathways and natural selection in shaping animal form. Quantitative-genetic analyses in several species have shown that interspecific and intraspecific differences in sex comb size are determined by multiple, as yet unidentified, loci (True et al 1997;Macdonald and Goldstein 1999;Nuzhdin and Reiwitch 2000;Coyne et al 2004;Tatsuta and TakanoShimizu 2006;Graze et al 2007). At the same time, developmental-genetic approaches are beginning to elucidate the molecular pathways involved in the specification and differentiation of sex combs (Barmina et al 2005;Barmina and Kopp 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many studies have found that a disproportionately large percentage of genes relating to speciation, reproductive isolation, and mate choice map to the sex chromosomes (Dobzhansky 1974;Templeton 1977;Coyne 1985;Coyne and Orr 1989;Prowell 1998;Reinhold 1998;Ritchie and Phillips 1998;Presgraves 2002). This may be because sex-linked incompatibility loci evolve at a faster rate than autosomal incompatability sites (Tao and Hartl 2003;Coyne et al 2004). …”
mentioning
confidence: 99%
“…The diagnostic differences between the species include male genital morphology and sex-comb tooth number (Lachaise et al 2000;Coyne et al 2004), but the most striking difference involves abdominal pigmentation. Among the nine species in the D. melanogaster subgroup, eight of them, including D. yakuba, have similar patterns of dark pigmentation: males possess thin black stripes along the posterior portions of tergites 2, 3, and 4, while tergites 5-7 are completely black.…”
mentioning
confidence: 99%